The Controversy of Students Learning Interest in English as a Future Career - Madina Maqfiroh; Ahmad Faruk (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study examines students’ learning interest in English and their perceptions of English as preparation for future careers across formal and non-formal educational contexts. A descriptive qualitative approach was employed, involving 30 participants consisting of 15 students from ECC Course and 15 undergraduate students from the English Education Study Program at Universitas KH. Mukhtar Syafaat. Data were collected through open-ended questionnaires, semi-structured interviews, and classroom observations, and analyzed using thematic analysis with data triangulation to ensure credibility. The findings reveal that most students recognize English as an important skill for academic and professional advancement. However, a contradiction was identified between students’ awareness of English as a career-related asset and their actual learning engagement, particularly due to grammar difficulties and classroom boredom. The study also found no major differences between students from the two educational contexts in terms of their perceptions and learning challenges. This study contributes to the field of EFL motivation by highlighting the gap between students’ awareness and their actual engagement in English learning. The findings suggest that more engaging, contextualized, and career-oriented teaching approaches are needed to enhance students’ learning interest and participation.